2017
DOI: 10.1590/0074-02760170062
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between the BACTEC MGIT 960 culture system with Genotype MTBDRplus and TB-SPRINT in multidrug resistant Mycobacterium tuberculosis clinical isolates from Brazil

Abstract: BACKGROUNDThe accurate detection of multidrug-resistant tuberculosis (MDR-TB) is critical for the application of appropriate patient treatment and prevention of transmission of drug-resistant Mycobacterium tuberculosis isolates. The goal of this study was to evaluate the correlation between phenotypic and molecular techniques for drug-resistant tuberculosis diagnostics. Molecular techniques used were the line probe assay genotype MTBDRplus and the recently described tuberculosis-spoligo-rifampin-isoniazid typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Our findings are in agreement with a review 24 that estimated pooled sensitivities and specificities for resistance prediction to RIF (91.3% and 97.1%) and INH (89.4% and 98.9%). Regarding the data from Brazil using the MTBDR plus in clinical isolates, our findings are comparable with a study 25 in the State of Minas Gerais, showing sensitivities of 93.3% for RIF, 83.3% for MDR or INH resistance detection, and 100% specificity for both drugs. A study on MDR-TB patients in Ribeirão Preto (SP), revealed 100% and 80% sensitivity in detecting RIF and INH resistance, respectively 26 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings are in agreement with a review 24 that estimated pooled sensitivities and specificities for resistance prediction to RIF (91.3% and 97.1%) and INH (89.4% and 98.9%). Regarding the data from Brazil using the MTBDR plus in clinical isolates, our findings are comparable with a study 25 in the State of Minas Gerais, showing sensitivities of 93.3% for RIF, 83.3% for MDR or INH resistance detection, and 100% specificity for both drugs. A study on MDR-TB patients in Ribeirão Preto (SP), revealed 100% and 80% sensitivity in detecting RIF and INH resistance, respectively 26 …”
Section: Discussionsupporting
confidence: 84%
“…In this study, rpo B Ser531Leu and kat G Ser315Thr mutations predominated, as in other settings 25 28 ) Identifying the specific mutation associated with drug resistance, which is not possible by phenotypic methods, may provide additional information on the category of resistance and guide therapeutic decision, as to the choice of the treatment regimen 29 .…”
Section: Discussionmentioning
confidence: 80%
“…GenoType MTBDR plus VER2.0 shows good accuracy for the detection of MDR isolates in smear-positive specimens (sensitivity between 83.3 and 96.4%, and specificity between 98.6 and 100%) (Bai et al, 2016; Nathavitharana et al, 2016; Dantas et al, 2017; Meaza et al, 2017). The Nipro NTM+MDRTB strips also show high specificity (between 97 and 100%) for INH and RIF resistance screening in cultured isolates and clinical (sputum) samples, but sensitivity varies between studies (from 50 to 95%) (Mitarai et al, 2012; Ruesch-Gerdes and Ismail, 2015; Nathavitharana et al, 2016).…”
Section: Molecular Assays For the Detection Of Drug Resistance In Mtbmentioning
confidence: 99%
“…This technique is a microbead-based assay developed to run on Luminex® devices (Luminex Corp., Austin, TX, USA) for the simultaneous spoligotyping and detection of rpoB , katG , and inhA mutations associated with resistance to RIF and INH. It has also been successfully used in previous studies and performed well when compared to the MTBDR plus [911] . However, no data on its accuracy and costs have been gathered from a multicenter laboratory study considering all components of the cost chain.…”
Section: Introductionmentioning
confidence: 99%